Cessation of extracorporeal photopheresis in chronic lung allograft dysfunction: effects on clinical outcome in adults (Swiss Medical Weekly, 2017)
BACKGROUND Extracorporeal photopheresis (ECP) has been reported to be safe and the ultimate treatment option in lung transplant recipients with chronic lung allograft dysfunction (CLAD), the main overall cause of mortality in lung transplant recipients. However, ECP is not reimbursed in selected health jurisdictions, and reimbursement by health insurance providers is a major issue. In Switzerland, ECP is not recognised by the health authorities as a therapy option for CLAD; thus by the end of 2014, ECP had to be stopped in the majority of adult lung transplant recipients cared for at the University Hospital Zurich because of lack of continuous funding. OBJECTIVE To describe the outcome of lung transplant recipients after forced cessation of ECP treatment. METHOD We retrospectively analysed outcome of 12 lung transplant recipients undergoing ECP for different phenotypes of CLAD (bronchiolitis obliterans syndrome, restrictive allograft syndrome) at our centre followed-up for 12 months after forced cessation of ECP. RESULTS Within the 12 months after treatment cessation, seven patients (58%) died with a median survival of 207 days (range 6–365 days). Lung function (FEV1, forced expiratory volume in 1 second) declined significantly 6 months after ECP cessation (p = 0.003). CONCLUSION Our data support the role of ECP as valuable treatment option in lung transplant recipients with CLAD.